CCP encyclopedia of Philippine art. - Alvero, Aurelio S. (1994)
This Volume 9 of the CCP encyclopedia covers the literatures of the different Philippine languages. It highlights the development of the principal literacy traditions in the Philippine and major key figures that affects Filipino consciousness.